A randomized controlled trial into the effects of neurofeedback, methylphenidate, and physical activity on EEG power spectra in children with ADHD. (8th January 2016) - Janssen, Tieme W. P.; Bink, Marleen; Geladé, Katleen; van Mourik, Rosa; Maras, Athanasios; Oosterlaan, Jaap
Abstract : Background: The clinical and neurophysiological effects of neurofeedback (NF) as treatment for children with ADHD are still unclear. This randomized controlled trial (RCT) examined electroencephalogram (EEG) power spectra before and after NF compared to methylphenidate (MPH) treatment and physical activity (PA) – as semi‐active control group – during resting and active (effortful) task conditions to determine whether NF can induce sustained alterations in brain function. Methods: Using a multicentre three‐way parallel group RCT design, 112 children with a DSM‐IV diagnosis of ADHD, aged between 7 and 13 years, were initially included. NF training consisted of 30 sessions of theta/beta training at Cz over a 10‐week period. PA training was a semi‐active control group, matched in frequency and duration. Methylphenidate was titrated using a double‐blind placebo controlled procedure in 6 weeks, followed by a stable dose for 4 weeks. EEG power spectra measures during eyes open (EO), eyes closed (EC) and task (effortful) conditions were available for 81 children at pre‐ and postintervention ( n  = 29 NF, n  = 25 MPH, n  = 27 PA). Clinical trials registration: Train Your Brain? Exercise and Neurofeedback Intervention for ADHD, https://clinicaltrials.gov/show/ ;NCT01363544, Ref. No. NCT01363544. Results: Both NF and MPH resulted in comparable reductions in theta power from pre‐ to postintervention during the EO condition compared to PA (ηp 2  = .08 and .12). For NF, greater reductions in theta were related to greater reductions in ADHD symptoms. During the task condition, only MPH showed reductions in theta and alpha power compared to PA (ηp 2  = .10 and .12). Conclusions: This study provides evidence for specific neurophysiological effects after theta/beta NF and MPH treatment in children with ADHD. However, for NF these effects did not generalize to an active task condition, potentially explaining reduced behavioural effects of NF in the classroom.